How Much can a Parent Bear? Cumulative Risk in Parental Burnout - Isabelle Roskam; Moïra Mikolajczak (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Parental burnout is a specific syndrome resulting from enduring exposure to chronic parenting stress. It encompasses three dimensions: an overwhelming exhaustion related to one’s parental role, an emotional distancing with one’s children and a sense of ineffectiveness in one’s parental role. This study aims at testing the cumulative effect of risk across five domains, i. e. sociodemographics, particularities of the child, stable traits of the parent, parenting and family functioning, related to parental burnout on its intensity. In a community-sample of 1,540 French-speaking parents, we examined parental burnout alongside with two cumulative risk indexes, i.e. unweighted and weighted, based on a set of 37 risk factors across the five domains. The results show that the number of risk factors that a parent is exposed to linearly predicts parental burnout regardless of the nature of these factors. Clinically, this means that no factor should be underestimated, the relieving impact of removing a series of “negligible factors” should not be underestimated either. At the prevention level, the current results also suggest that interventions or public policies targeting one factor will be less efficient than those targeting several factors at once.